PENGARUH MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DAN KONVENSIONAL TERHADAP PRESTASI BELAJAR SISWA DITINJAU DARI MINAT BELAJAR PADA MATA PELAJARAN IPS KELAS VIII MTs NEGERI DI KABUPATEN KUDUS - ANIFAH, NOOR (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The purpose of this research are to: (1) The effect of STAD models of learning achievement in terms of interest in learning social studies eighth grade students a semester MTsN Kudus District. (2) Effect of conventional learning model to learning achievement in terms of interest in learning social studies eighth grade students a semester MTsN Kudus District. (3) the effect of STAD and conventional learning models of learning achievement in terms of interest in learning in social studies class VIII semester se MTsN Kudus District. This study is an experimental study. Its population is students MTsN 1 and MTsN 2 Kudus Kab. Methods of data collection using the quesioner and test methods. Analysis using two- way analysis of variance. Based on the analysis and discussion of hypothesis testing can be concluded: (1) There are significant differences in the social studies achievement using STAD model group and the conventional group. Student learning outcomes in social studies with STAD model is better than the students who used conventional models. (2) There are significant differences in the group of social studies achievement of students with a high interest in learning and a group of students with low interest in learning. Student learning outcomes in social studies subjects who have a high interest in learning is better than the students who had low interest in learning. (3) There is interaction between the model of learning with interest in learning to learning achievement IPS. Learning achievement in social studies subjects in group STAD model with a high interest in learning has the highest average value, while the conventional model with a low interest in learning has the lowest average value.Â Keywords: Type STAD Cooperative Learning Model, Conventional, Interest in Learning, Learning Achievement IPS.